Clinical and hemodynamic effects of carvedilol in patients with hypertrophic cardiomyopathy - T. A. Abdullaev; O. Kh. Allaberganov; B. U. Mardanov; R. D. Kurbanov (Кардиоваскулярная терапия и профилактика, 1970)
Aim. To study carvedilol effectiveness in patients with hypertrophic cardiomyopathy (HCMP). Material and methods. The study included 52 patients with HCMP (67% men and 33% women; mean age 40,7±3,1 yeas). All participants underwent clinical examination, six-minute walk test (6mwt), standard 12-lead electrocardiography (ECG), echocardiography (EchoCG), chest X-ray with cardio-thoracic index calculation, and angina severity assessment using a verbal assessment scale (VAS). All patients were divided into two groups: Group I (n=38) with interventricular wall thickness (IVWT) ≤20 mm; and Group II (n=14) with IVWT >20 mm. Carvedilol was titrated from the minimal dose of 6,25 mg/d to the maximal dose of 31,25 mg/d (b. i.d.). The treatment duration was 12 weeks. Results. Carvedilol therapy was associated with an improvement of clinical and hemodynamic parameters (including reduced angina severity and improved left ventricular diastolic function, LVDF) in both groups. The effectiveness of conservative treatment was higher in patients with IVWT <20 mm. Conclusion. In HCMP patients, the severity of clinical symptoms and non-specific ECG disturbances increased in parallel with the IVW hypertrophy progression. Carvedilol therapy demonstrated beneficial effects on clinical status, cardiac hemodynamics, and LVDF. These effects were maximal in patients with IVWT <20 mm.